Desain Small-Scale Chemistry Pada Pembelajaran Praktikum Kimia Umum - Julia Mardhiya; Fadhillah Nur Laila (Postgraduate, University of Mataram, 2022)
Hands-on chemistry activity or practical work is an important aspect of teaching at the high school and college level as part of the science education curriculum. This study aims to design Small-scale Chemistry (SSC) for general chemistry practical work. The product are laboratory work manual and practical kit. The development model used is ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). At the analysis stage, five experiment will be designed to become SSC. There are five experiments, namely determining the order of the reaction, observation the shift in chemical equilibrium, identification acid-base with indicators, determining the strength of the acid and water electrolysis. The feasibility of the manual and practical kit in content feasibility (0.84), language feasibility (0.90), presentation feasibility (0.84), graphic feasibility (0.90), and kit feasibility (0.94). All are categorized as valid based on the validity criteria of Aiken's V. The results of the implementation show that the SSC design can be implemented and the results can be observed for General Chemistry experiment learning activities. The chemicals used for the experiment are far less than the macro-scale practical work. This is in accordance with the SSC principle.